Work-related respiratory symptoms and lung function among solderers in the electronics industry: a meta-analysis - Mendy, Angelico (Springer Japan, 2011)
OBJECTIVE: Research on the respiratory effect of exposure to solder fumes in electronics workers has been conducted since the 1970s, but has yielded inconsistent results. The aim of this meta-analysis was to clarify the potential association. METHODS: Effect sizes with corresponding 95% confidence intervals (CIs) for odds of respiratory symptoms related to soldering and spirometric parameters of solderers were extracted from seven studies and pooled to generate summary estimates and standardized mean differences in lung function measures between exposed persons and controls. RESULTS: Soldering was positively associated with wheeze after controlling for smoking (meta-odds ratio: 2.60, 95% CI: 1.46, 4.63) and with statistically significant reductions in forced expiratory volume in 1 s (FEV1) (−0.88%, 95% CI: −1.51, −0.26), forced vital capacity (FVC) (−0.64%, 95% CI: −1.18, −0.10), and FEV1/FVC (−0.35%, 95% CI: −0.65, −0.05). However, lung function parameters of solderers were within normal ranges [pooled mean FEV1: 97.85 (as percent of predicted), 95% CI: 94.70, 100.95, pooled mean FVC: 94.92 (as percent of predicted), 95% CI: 81.21, 108.64, and pooled mean FEV1/FVC: 86.5 (as percent), 95% CI: 78.01, 94.98]. CONCLUSIONS: Soldering may be a risk factor for wheeze, but may not be associated with a clinically significant impairment of lung function among electronics workers.